Ghrelin-Reactive Immunoglobulins in Conditions of Altered Appetite and Energy Balance - Fetissov, Sergueï O.; Lucas, Nicolas; Legrand, Romain (Frontiers in Endocrinology, 2017)
Part of circulating ghrelin is bound to immunoglobulins (Ig) protecting it from degradation and preserving its functional activity. This review summarizes the data on ghrelin- and desacyl- ghrelin-reactive IgG in conditions of altered appetite and energy balance. Plasma levels and affinity kinetics of such IgG were compared in patients with obesity and anorexia nervosa and in animal models of obesity including ob/ob mice, high-fat diet- induced obese mice and obese Zucker rats as well as in mice after chronic food restriction and activity-based anorexia and in rats with methotrexate-induced anorexia. We show that plasmatic IgG in both obese humans and animals are characterized by increased affinity for ghrelin. In contrast, patients with anorexia nervosa and anorectic rodents all show lower affinity of ghrelin- and desacyl-ghrelin- reactive IgG, respectively, the changes which were not observed in non-anorectic, chronically starved mice. We also show that affinity of ghrelin-reactive IgG correlate with plasma levels of ghrelin. These data point to common mechanisms underlying modifications of affinity kinetics properties of ghrelin-reactive IgG during chronic alterations of energy balance in humans and rodents and support a functional role of such autoantibodies in ghrelin-mediated regulation of appetite.